2020
DOI: 10.21203/rs.3.rs-22056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

City Lockdown and Nationwide Intensive Community Screening Are Effective In Controlling COVID-19 Epidemic: Analysis Based on A Modified SIR Model

Abstract: In December 2019, an outbreak of COVID-19 epidemic occurred in Wuhan, China and this infection has spread rapidly into more than 109 countries around the world.To limit the rapid spread in community and nationwide, Wuhan city lockdown and nationwide intensive community screening were employed by Chinese government.To assess the effectiveness of city lockdown and intensive community screening, we built a modified SIR model by introducing an α value into the classic SIR model. The α value represents the proporti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…This is also shown in the word cloud in Figure 4. The work of Lamsal (2020b) [11] , Peng et al (2020) [22] , Barkur (2020) [2] , and Dubey (2020) [4] all reported an overall positive sentiment on the nationwide lockdown due to COVID19. This shows that the lockdown exercise, though with some economic effects on the nations, was an acceptable control measure in the fight against the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is also shown in the word cloud in Figure 4. The work of Lamsal (2020b) [11] , Peng et al (2020) [22] , Barkur (2020) [2] , and Dubey (2020) [4] all reported an overall positive sentiment on the nationwide lockdown due to COVID19. This shows that the lockdown exercise, though with some economic effects on the nations, was an acceptable control measure in the fight against the pandemic.…”
Section: Resultsmentioning
confidence: 99%
“…In another study which focused on the current coronavirus global pandemic, Peng et al (2020) [22] built a modified Susceptible Infected and Recovered (SIR) model from the classic SIR model by introducing a "proportion of the infected that is not effectively isolated from the susceptible at a given time point". Apart from the study's validation of the effectiveness of the city lockdown and intensive community screening approaches in China, it also predicted an exponential increase of infection cases in Italy and South Korea if the city lockdown and intensive community screening approaches are not followed.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…The SEIR model divides people into four compartments: susceptible, exposed, infectious, and removed 18 ; it has been applied to many virus outbreaks such as MERS 19,20 and SARS 21,22 , which established its public prominence [23][24][25] . However, as these classical models do not consider the unique features of COVID-19, many studies have built upon them by introducing new parameters or new groups into the existing models to represent more types of population, which can assist in representing reality more accurately [26][27][28] .…”
Section: Introductionmentioning
confidence: 99%